2017
DOI: 10.5812/jjcdc.63304
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Heath Team in Coping Process of Family Caregivers with Patients Under Hemodialysis: A Qualitative Study

Abstract: Background: The high dependence of hemodialysis patients on home caregivers is a great source of care burden for them; therefore, accountability with appropriate communication as well as appropriate behavior and attention to needs of caregiver by health care team is a serious impact on care burden. Methods: A content analysis approach was used for data collection and analysis. The participants included16 family caregivers selected through purposive sampling from 4 medical education centers affiliated with Ahva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Family is the best source of care for HD patients and given the long process of kidney failure, emergence of new needs, and major changes in normal life style and routine, family members of these patient experience numerous stresses. In this regard, the coping skills play a notable role in dealing with the challenges and improving mental health of family members (14).…”
Section: Introductionmentioning
confidence: 99%
“…Family is the best source of care for HD patients and given the long process of kidney failure, emergence of new needs, and major changes in normal life style and routine, family members of these patient experience numerous stresses. In this regard, the coping skills play a notable role in dealing with the challenges and improving mental health of family members (14).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research regarding caregivers of chronic patients' adaptation is limited, and the focus is more on quantitative studies than the experiences of caregivers [20]. Qualitative research is the appropriate method to access individuals' lived experience and their inner world.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Living with hemodialysis is a permanent challenge due to the existence of a treatment plan, its complications, and dietary constraints. [ 8 ] Therefore, patients’ quality of life is affected by physical and mental problems caused by these challenges. [ 9 ] Studies have shown that this group of patients often experience problems including economic issues, difficulty in maintaining a job, reduction of libido and impotence, depression due to chronic illnesses, and fear of death.…”
Section: Introductionmentioning
confidence: 99%